Use of high-speed connectivity to global academic network for research and education in Central Asia - A. Kutanov (MANAS: Journal of Engineering)
The EC Project Central Asian Research and Education Network (CAREN) is aimed to establish high speed data transmission regional network for Central Asian countries, and connect it to European research network GEANT. Today, the Central Asian Research and Education Network(CAREN) is upgrading ancient Silk Road to a 21st - century high-speed internet highway for research and educational institutions through the region. CAREN catalyzed regional cooperation among academic communities of Central Asian countries in such areas as environmental monitoring, distance learning, telemedicine, e- culture, networking and etc. Cooperation between academic communities of Central Asia and other regions of the world using CAREN connectivity is demonstrated